Global citizenship education: An educational theory of the common good? A conversation with Carlos Alberto Torres. Issue 6 (September 2019) - Bosio, Emiliano; Torres, Carlos Alberto
This paper presents a remarkable conversation with Carlos Alberto Torres about Global Citizenship Education (GCE) in relation to research, teaching, and learning in the USA. Torres is a Distinguished Professor of Education, UNESCO UCLA Chair on Global Learning and Global Citizenship Education, UCLA and Founding Director of the Paulo Freire Institute (São Paulo; Buenos Aires; UCLA). In this dialogue, he artfully blends together theoretical and practical perspectives on global citizenship focused on the connection between culture and power, the interrelationships of economic, political and cultural spheres in the modern educational institutions in the context of growing internationalization and globalization of education offering an exclusive portrait of GCE as a site of permanent pursuit for social justice. Our tête-à-tête is presented as a pedagogical tool for discussion that invites educators to reflect critically on the possible origins and implications of GCE discourses they are exposed to. It is designed with the intent to contribute toward the possibility of imagining a "yet-to-come" post-colonial, critical-transformative, and value-creating GCE-curriculum beyond a Westernized, market-oriented and apolitical practices toward a more sustainable paradigm based on principles of mutuality and reciprocity, or as Torres calls it in this discussion "el buen vivir"—a concept that portrays a way of acting in society that is community-centric, ecologically balanced, and culturally sensitive, in the ongoing construction of a more just and peaceful world.